Plasmodium falciparum Drug Resistance Genes pfmdr1 and pfcrt In Vivo Co-Expression During Artemether-Lumefantrine Therapy - Silva, M.; Malmberg, M.; Otienoburu, S. D.; Björkman, A.; Ngasala, B.; Mårtensson, A.; Gil, J. P.; Veiga, M. I. (Frontiers in Pharmacology, 2022)
Background: Artemisinin-based combination therapies (ACTs) are the global mainstay treatment of uncomplicated Plasmodium falciparum infections. PfMDR1 and PfCRT are two transmembrane transporters, associated with sensitivity to several antimalarials, found in the parasite food vacuole. Herein, we explore if their relatedness extends to overlapping patterns of gene transcriptional activity before and during ACT administration. Methods: In a clinical trial performed in Tanzania, we explored the pfmdr1 and pfcrt transcription levels from 48 patients with uncomplicated P. falciparum malaria infections who underwent treatment with artemether-lumefantrine (AL). Samples analysed were collected prior to treatment initiation and during the first 24 hours of treatment. Frequency of PfMDR1 N86Y and PfCRT K76T was determined through PCR-RFLP or direct amplicon sequencing. Gene expression was analysed by real-time quantitative PCR. Results: A wide range of pre-treatment expression levels was observed for both genes, approximately 10-fold for pfcrt and 50-fold for pfmdr1. Additionally, a significant positive correlation demonstrates pfmdr1 and pfcrt co-expression. After AL treatment initiation, pfmdr1 and pfcrt maintained the positive co-expression correlation, with mild downregulation throughout the 24 hours post treatment. Additionally, a trend was observed for PfMDR1 N86 alleles and higher expression before treatment initiation. Conclusion: pfmdr1 and pfcrt showed significant co-expression patterns in vivo, which were generally maintained during ACT treatment. This observation points for relevant related roles in the normal parasite physiology, which seem essential to be maintained when the parasite is exposed to drug stress. Additionally, keeping the simultaneous expression of both transporters might be advantageous for responding to the drug action.